Combining on-foot porters with vans for last-mile parcel deliveries: results of a study in central London. (27th February 2021) - Allen, Julian; Piecyk, Maja; Piotrowska, Marzena; Cherrett, Tom; McLeod, Fraser; Oakey, Andrew; Bates, Oliver; Friday, Adrian; Cheliotis, Kostas; Wise, Sarah; Bektas, Tolga
Parcel delivery operations in central London currently involve drivers using vans which are parked at the kerbside for up to 60% of the round time while drivers make deliveries on-foot to consignees, walking up to 10 km per day. A trial was carried out in which deliveries were made by on-foot porters using wheeled bags supplied by van. Results of this trial and additional analysis of its wider implementation across central London indicate that parcel portering could result in reductions in vehicle parking time at kerbside (of 50-65%), and vehicle driving time and distance travelled (of 25-35%) compared to current operations. Such outcomes would result in improvements in greenhouse gas emissions and local air quality. Related planning considerations for public policy makers including reviewing vehicle kerbside stopping regulations to encourage portering, and the provision of land for secure storage facilities for porter's bags are identified and discussed.